Preliminary in vitro and in vivo assessment of a new targeted inhibitor for choroidal neovascularization in age-related macular degeneration - Li W; Dong L; Ma M; Hu B; Lu Z; Liu X; Liu J; Li X (Dove Medical Press, 2016)
Wenbo Li,1,* Lijie Dong,1,* Minwang Ma,2,* Bojie Hu,1 Zhenyu Lu,3 Xun Liu,1 Juping Liu,1 Xiaorong Li1 1Tianjin Medical University Eye Hospital, Tianjin, People’s Republic of China; 2Affiliated Hospital of Medical College of Chinese People’s Armed Police Forces (CapF), Tianjin, People’s Republic of China; 3Tianjin Precision Cell Biotechnology Co. Ltd., Tianjin, People’s Republic of China *These authors contributed equally to this work Abstract: Choroidal neovascularization (CNV) in age-related macular degeneration usually causes blindness. We established a novel targeted inhibitor for CNV in age-related macular degeneration. The inhibitor CR2-sFlt 1 comprises a CR2-targeting fragment and an anti-vascular endothelial growth factor (VEGF) domain (sFlt 1). The targeting of CR2-sFlt 1 was studied using the transwell assay in vitro and frozen sections in vivo using green fluorescent labeling. Transwell assay results showed that CR2-sFlt 1 migrated to the interface of complement activation products and was present in the retinal tissue of the CR2-sFlt 1-treated CNV mice. Treatment effects were assessed by investigating the VEGF concentration in retinal pigmented epithelial cell medium and the thickness of the CNV complex in the mice treated with CR2-sFlt 1. CR2-sFlt 1 significantly reduced the VEGF secretion from retinal pigmented epithelial cells in vitro and retarded CNV progress in a mouse model. Expression analysis of VEGF and VEGFRs after CR2-sFlt 1 intervention indicated the existence of feedback mechanisms in exogenous CR2-sFlt 1, endogenous VEGF, and VEGFR interaction. In summary, we demonstrated for the first time that using CR2-sFlt 1 could inhibit CNV with clear targeting and high selectivity. Keywords: choroidal neovascularization, macular degeneration, complement activation, vascular endothelial growth factor